How precariously employed gay, bisexual, and queer immigrant and refugee men in Toronto make meaning of work, health, and wellbeing - Amy Xu; David J. Kinitz; Basak Yanar; Sonja Senthanar; Yvonne Su; Roya Haghiri-Vijeh (Scientific Reports, 2026)
Abstract Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) people experience mental health and trauma outcomes as a result of systemic exclusion from the labour market in Canada, with less known about intersectional labour precarity for LGBTQ+ immigrants. How LGBTQ+ immigrants experiencing intersectional precarity appraise work, health, and wellbeing challenges is unknown. Drawing from 13 interviews conducted in 2021 and utilizing Park’s meaning making model as a framework, this qualitative study focuses on gay, bisexual, and queer immigrant and refugee men experiencing precarious employment in Toronto, Canada, to ask the following question: how do participants make meaning of their work, health, and wellbeing experiences? Participants were primarily highly educated and commonly arrived in Canada on refugee status or immigrated to live without persecution of their sexual orientation and/or gender identity. Through reflexive thematic analysis, we identified two meanings made from participant narratives: ambivalence towards the presumed superiority of the standard employment relationship and valuing the possibility of leveraging precarious work. Implications of our findings include the risk of meaning making loops without situational change or intervention and the opportunity for collaboration between social service and healthcare professionals working with populations made vulnerable through intersecting systems of marginalization.